The impact of active surveillance and health education on an Ebola virus disease cluster — Kono District, Sierra Leone, 2014–2015. Issue 1 (December 2016) - Stehling-Ariza, Tasha; Rosewell, Alexander; Moiba, Sahr; Yorpie, Brima; Ndomaina, Kai; Jimissa, Kai; Leidman, Eva; Rijken, Dingeman; Basler, Colin; Wood, James; Manso, Dumbuya
Abstract Background During December 2014–February 2015, an Ebola outbreak in a village in Kono district, Sierra Leone, began following unsafe funeral practices after the death of a person later confirmed to be infected with Ebola virus. In response, disease surveillance officers and community health workers, in collaboration with local leadership and international partners, conducted 1 day of active surveillance and health education for all households in the village followed by ongoing outreach. This study investigated the impact of these interventions on the outbreak. Methods Fifty confirmed Ebola cases were identified in the village between December 1, 2014 and February 28, 2015. Data from case investigations, treatment facility and laboratory records were analyzed to characterize the outbreak. The reproduction number (R) was estimated by fitting to the observed distribution of secondary cases. The impact of the active surveillance and health education was evaluated by comparing two outcomes before and after the day of the interventions: 1) the number of days from symptom onset to case-patient isolation or death and 2) a reported epidemiologic link to a prior Ebola case. Results The case fatality ratio among the 50 confirmed Ebola cases was 64.0 %. Twenty-three cases occurred among females (46.0 %); the mean age was 39 years (median: 37 years; range: 5 months to 75 years). Forty-three (87.8 %) cases were linked to the index case; 30 (61.2 %) were either at the funeral of Patient 1 or had contact with him while he was ill. R was 0.93 (95 % CI: 0.15–2.3); excluding the funeral, R was 0.29 (95 % CI: 0.11–0.53). The mean number of days in the community after onset of Ebola symptoms decreased from 4.0 days (median: 3 days; 95 % CI: 3.2–4.7) before the interventions to 2.9 days (median: 2 days; 95 % CI: 1.6–4.3) afterward. An epidemiologic link was reported in 47.6 % of case investigations prior to and 100 % after the interventions. Conclusions Initial case investigation and contact tracing were hindered by delayed reporting and under-reporting of symptomatic individuals from the community. Active surveillance and health education contributed to quicker identification of suspected cases, interrupting further transmission.